Nanolithography of biointerfaces. (27th August 2019) - Feizi, Ten
Abstract : This article is based on the Concluding remarks made at the Faraday Discussion meeting on Nanolithography of Biointerfaces, held in London, UK, 3–5 th July 2019. Abstract : This article is based on the Concluding remarks made at the Faraday Discussion meeting on Nanolithography of Biointerfaces, held in London, UK, 3–5 th July 2019.